LEARNING DESIGN OF LINEAR DIOPHANTINE EQUATION BY SCIENTIFIC APPROACH - HIDAYAT (NIM : 90111001); Pembimbing : Dr. Janson Naiborhu, AGUS
This project discusses the solution of diophantine equation by using Euclidean algorithm and division. Diophantine equation that will be discussed only for linear equation. In this project developed a learning of linear diophantine equation by using the scientific approach with discovery learning model, ask and answer method and group discussion. Its result presentated in the learning scenario.